Serum prostate specific antigen is a good indicator of prostatic volume in men with benign prostatic hyperplasia - Ebenezer Abotsi; Kekeli K. Adanu; Eyram C. Bansah (AOSIS, 2022)
Background: Benign prostatic hyperplasia (BPH) is the most common cause of bladder outlet obstruction in men over the age of 50 years. An association between the prostate specific antigen (PSA), International Prostate Symptoms Score (IPSS) and prostate volume (PV) may be instrumental in determining patients who may benefit from treatment. Targeted therapy will reduce the cost of care because it is unwise to treat all men with prostate enlargement to prevent complications when the risk of occurrence is negligible. Aim: To determine the correlation between the PSA, IPSS and PV in men of African descent. Setting: This was a cross sectional analysis involving 92 patients diagnosed as having symptomatic BPH at the Ho Teaching Hospital. Methods: The data were collected using standardised questionnaires. The IPSS determined urinary symptom severity. The PV was determined using a transabdominal ultrasound machine. Serum PSA was retrieved from the electronic medical records. Results: The mean PV was 61.04 cm3 ± 21.95 cm3, the mean PSA was 4.21 ng/mL ± 3.85 ng/mL, and mean IPSS of 21.59 ± 3.78. The Pearson's correlation between PV and PSA was 0.283 (p = 0.01), between PV and IPSS was 0.108 (p = 0.30), and finally, between Serum PSA and IPSS Score was −0.086 (p = 0.42). Conclusion: This study showed that serum PSA has a positive correlation with PV. However, IPSS had no significant association with PSA or PV in patients with BPH. Contribution: This study provides insights into the implications of clinical parameters on the management of prostate enlargement.